Dark matter phenomenology in 2HDMS in light of the 95 GeV excess - Juhi Dutta; Jayita Lahiri; Cheng Li; Gudrid Moortgat-Pick; Sheikh Farah Tabira; Julia Anabell Ziegler (European Physical Journal C: Particles and Fields)
Abstract The Two Higgs Doublet model extended with a complex scalar singlet (2HDMS) is a well-motivated Beyond Standard Model candidate addressing several open problems of nature. In this work, we focus on the dark matter (DM) phenomenology of the complex scalar singlet where the real part of the complex scalar obtains a vacuum expectation value. The model is characterized by an enlarged Higgs spectrum comprising six physical Higgs bosons and a pseudoscalar DM candidate. We address the impact of accommodating the 95 GeV excess on the 2HDMS parameter space and DM observables after including all theoretical and experimental constraints. Finally, we look into the prospects of this scenario at HL-LHC and future lepton colliders for a representative benchmark.